Military Integration, Demobilization, and the Recurrence of Civil War. Issue 1 (1st January 2019) - Bussmann, Margit
ABSTRACT: Peace agreements often include provisions for the military integration of the conflict parties, involving an increase in government forces, and at the same time requesting demobilization and thus a reduction of military personnel. Depending on the modalities and magnitude both can be strong signals of a commitment to the peace process. However, tensions between these two concepts can also endanger post-conflict stability. The empirical analyses of 77 post-conflict societies show that civil war is more likely to recur if rebel forces are kept separate during the military integration process and if the military plays an important role in post-conflict economies.